Healing Process of Autogenous Bone Graft in Spontaneously Hypertensive Rats Treated With Losartan: An Immunohistochemical and Histomorphometric Study - Gealh, Walter Cristiano [UNESP]; Silva Pereira, Cassiano Costa [UNESP]; Luvizuto, Eloa Rodrigues [UNESP]; Garcia-Junior, Idelmo Rangel [UNESP]; Silva, Cristina Antoniali [UNESP]; Okamoto, Roberta [UNESP] (Elsevier B.V., 2014)
Purpose: Hypertension is a major risk factor for cardiovascular diseases, which has been related to such changes as gradual bone loss and a decrease in bone mass index. The cellular and molecular mechanisms that involve hypertension and osteoporosis are not fully understood. Many patients have high blood pressure, controlled or uncontrolled, and may use at least 1 antihypertensive drug, and an understanding of the interference of hypertension with bone healing is very important when considering oral rehabilitation with implants and bone grafts. This study investigated the interference of hypertension in bone metabolism during the repair process of autogenous bone grafting and analyzed the influence of losartan, an antihypertensive drug and angiotensin II receptor antagonist, through histometric and immunohistochemical analyses by examining the protein expressions of osteocalcin, osteoprotegerin, receptor activator of nuclear factor-kappa B, receptor activator of nuclear factor-kappa B ligand, tartrate-resistant acid phosphatase, vascular endothelial growth factor, and platelet endothelial cell adhesion molecule.Materials and Methods: The groups studied include 24 normotensive Wistar rats and 24 spontaneously hypertensive rats divided into groups treated and not treated with losartan. Rats were subjected to block bone graft surgery in the mandible and were sacrificed at 7, 14, and 28 days.Results: Histometric analysis was performed to evaluate the amount of bone tissue formed at the interface of the recipient bed and bone graft. The total area of formed bone tissue was outlined and calculated. Immunohistochemical analysis was semi-quantitative and the significance of the differences between groups regarding the percentage of newly formed bone tissue interface and protein expression were determined by ANOVA analysis of variance and Kruskall-Wallis followed by Tukey test or Holm Sidak to detect differences between groups. The results were considered statistically significant when P < .05.Conclusion: The untreated hypertensive rats showed a delay in the repair of autogenous bone block grafts compared with untreated Wistar rats. Furthermore, the use of losartan for lowering blood pressure in these animals was shown to improve the healing process, despite not showing important statistical differences. Crown Copyright (C) 2014 Published by Elsevier Inc on behalf of the American Association of Oral and Maxillofacial Surgeons. All rights reserved